Leveraging neuroscience education to address stigma related to opioid use disorder in the community: a pilot study - Kyzar, Evan J.; Arbuckle, Melissa R.; Abba-Aji, Adam; Balachandra, Krishna; Cooper, Joseph; Dela Cruz, Adriane; Edens, Ellen; Heward, Brady; Jibson, Michael; Jordan, Ayana; Moreno-De-Luca, Daniel; Pazderka, Hannah; et al. (Frontiers in Psychiatry, 2024)
Opioid use disorder (OUD) and overdose deaths are a public health crisis. One contributing factor is stigma towards people who use opioids. We developed and conducted a public-facing, half-day educational event designed to challenge misperceptions about OUD from a contemporary neuroscience perspective. Participants engaged with three different resources on the neurobiology of addiction; at the end of the event, they rated its effectiveness. We also collected and compared pre-and postevent composite OUD stigma scales. Participants rated our approach and the overall event as highly effective. Additionally, OUD stigma scores were lower immediately following the event, and this decrease was primarily driven by decreased internalized stigma. Here, we demonstrate an effective proof-of-concept that an accessible, publicfacing, neuroscience education event may reduce OUD stigma in the community.